PASAR CAH CILIK” PEMBUATAN MINUMAN ES CINCAU DENGAN PENAMBAHAN SARI BUAH IDE WIRAUSAHA UNTUK SISWA DI SDN 01 BABAKAN KECAMATAN KRAMAT KABUPATEN TEGAL - Lusi Nur Astriansyah; Lyswidia Andriarsih (CV. ALIM'SPUBLISHING, 2023)
students need higher nutrition, increased growth and physical development, affecting intake and nutritional needs. Can be overcome with drinks made from natural ingredients. To determine the fiber content, nutrition and acceptability of grass jelly drinks with the addition of beets and soursop. With the addition of natural grass jelly extract, namely beetroot, soursop, the nutritional value of the formulation was tested for fiber content and its proximate value. Chopped beet products produce a fiber content of 1.48% and this product can be said to be a source of fiber if consumed per 250 ml or around 3.7 g of fiber. This is in accordance with BPOM.